2022
DOI: 10.3390/ijms23073936
|View full text |Cite
|
Sign up to set email alerts
|

Glycoproteomic and Phenotypic Elucidation of B4GALNT2 Expression Variants in the SID Histo-Blood Group System

Abstract: The Sda histo-blood group antigen (GalNAcβ1-4(NeuAcα2-3)Galβ-R) is implicated in various infections and constitutes a potential biomarker for colon cancer. Sd(a−) individuals (2–4% of Europeans) may produce anti-Sda, which can lead to incompatible blood transfusions, especially if donors with the high-expressing Sd(a++)/Cad phenotype are involved. We previously reported the association of B4GALNT2 mutations with Sd(a−), which established the SID blood-group system. The present study provides causal proof under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Reasonably, it is possible that differences in the regulatory regions of the B4GALNT2 gene allow a stronger expression in these individuals. However, neither the coding sequence nor the 2000 bp upstream genomic region of the B4GALNT2 gene in 5 Cad + individuals revealed common alterations potentially accounting for their Cad status [23]. In conclusion, some of the Sd a-phenotypes are due to mutations in the coding sequence of B4GALNT2, but the origin of other cases remains obscure [6].…”
Section: Why Some People Are Sd A-?mentioning
confidence: 80%
See 1 more Smart Citation
“…Reasonably, it is possible that differences in the regulatory regions of the B4GALNT2 gene allow a stronger expression in these individuals. However, neither the coding sequence nor the 2000 bp upstream genomic region of the B4GALNT2 gene in 5 Cad + individuals revealed common alterations potentially accounting for their Cad status [23]. In conclusion, some of the Sd a-phenotypes are due to mutations in the coding sequence of B4GALNT2, but the origin of other cases remains obscure [6].…”
Section: Why Some People Are Sd A-?mentioning
confidence: 80%
“…Transfection of the p.Cys466Arg mutant form failed to turn a Sd a-cell line into a Sd a+ status. Unexpectedly, both p.Gln436Arg and p.Arg523Trp mutant forms induced a Sd a expression level comparable with wild type [23]. Another important question regards the origin of the Cad status.…”
Section: Why Some People Are Sd A-?mentioning
confidence: 95%
“…The constructs used in this study were obtained from GeneCopoeia (Rockville, MD, USA; vector made by Labomics; Nivelles, Belgium) and based on ABO*A1.01 (NG_006669.1) and B.01 consensus sequences with the addition of the investigated variants (Table 1). Plasmid constructs were amplified and purified according to Stenfelt et al 16 Sequences of vector inserts were confirmed by Eurofins Genomics (Ebersberg, Germany), using Sanger sequencing, with primers M61‐F (5'‐GCGGTAGGCGTGTACGGT) and M61‐R (5'‐AGCAGTCCCCAAGTCAGT).…”
Section: Methodsmentioning
confidence: 99%
“…Expression and glycoproteomic studies with B4GALNT2 constructs with wild‐type sequence or the predominant null candidate variant c.1396C were performed in HEK293 cells [7]. While the consensus ‘wild‐type’ allele induced expression of the antigen, the c.1396C construct did not.…”
Section: New Blood Group Systemsmentioning
confidence: 99%